Bentuk Tuturan Pembuka dan Penutup Pengamen di Bus Antar Kota (Bojonegoro-Surabaya) - Umamy, Etty; Pangestutik, Dwi (Jurnal Likhitaprajna, 2023)
Humans express ideas and thoughts through language. Language is clearly visible in a person's speech; this is closely related to his field or work. One type of utterance is the utterance delivered by buskers. The focus of this research is to study the forms of the opening and closing speeches of buskers on inter-city buses (Bojonegoro-Surabaya). This iresearch is iqualitative iresearch iwith a icase study type. The idata isources ifor ithis iresearch iare the ispeeches of istreet isingers iand the contexti of the isituations ithat iinfluence ithem. Data icollection isi done iby recordingi, observingi, and itaking notes. iData ianalysis itechniques in ithis istudy used an iinteractive imodel iconsisting of idata icollection, idata ireduction, idata presentationi, iand idrawing iconclusions. What can be concluded is that the form of opening speech in busking activities includes greetings, apologies, and conveying hopes. While the form of closing speech in busking activities includes saying greetings of thanks, apologizing, expressing hopes, and conveying appeals.